Pengaruh Teknologi Informasi, Pemahaman Investasi, Financial Literacy, Motivasi Investasi, Modal Minimal Terhadap Minat Investasi - Octavatiya, Audrey Jennifer; Mulyanto, Mulyanto; Ashsifa, Izza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to examine and analyze the influence of information technology, investment understanding, financial literacy, investment motivation, and minimum capital on student investment interest (study on Accounting students in Kudus Regency). In this study, sampling techniques using purposive sampling method. The sample used was 350 respondents. The object of this study is accounting students in Kudus Regency. The type of research used in this study is quantitative by using primary data obtained directly by distributing questionnaires directly to respondents, namely students of accounting courses in universities located in Kudus Regency. Data processing techniques in this study using SEM-PLS and this data is processed using SmartPLS application version 4.1.0.2. The results of this study indicate the influence of information technology with a T value of 6.209; Investment understanding of 1.976; Financial Literacy of 3.295; Investment motivation of 2.773; Minimum capital of 2.954; on investment interest, with a p-value <0.05. So that the results obtained investment understanding, financial literacy, investment motivation, and minimum capital have a positive effect on investment interest. These results are in line with the Theory of planned behaviour developed by Ajzen in 1985 which is the development of the theory of reason action (TRA) to predict and explain goal-directed behaviour. TPB is also the intention to carry out an action will be influenced by individual attitudes towards behaviour, subjective norms, and perceived behavioural control.